Peran International Civil Aviation Organization dalam Penanganan Kasus Penembakan Penerbangan Sipil Internasional Studi Kasus: Penembakan Pesawat Malaysia Airlines MH17 Tahun 2014 - Yoga, Arland; Putranti, Ika Riswanti; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Aircraft incident has a less probability than other transportation. However, it has greaterimpact when it is occured. Like aircraft incident that happen to Malaysia Airlines flightMH17. That aircraft had been declared missing when flight toward Dnipropetrovskairspace in Ukraina. After the search, the aircraft went completely dispatch and all thepassenger and flight crew had lost their life. Looking through the Annex 13 of Conventionon International Civil Aviation, rights and responsibility of state when the aircraft incidenthappen and the investigation can be held by several different country particularly theaircraft is on international flight. Therefore, role of international organization is needed tointercede and coordinate states that involved. ICAO is an international organizationspecialized on aviation aspect. ICAO necessarily have a role on the case handle of MH17shootdown. This research have a purpoce to seek the role of ICAO on the case handle ofMH17 shootdown. With the perspective of Neoliberalism Institutionalism, will be knownthe role of ICAO on handling the case. Both the roles performed before and after theshootdown occurred as well as after the investigation report was issued. Methodological ofthis research is qualitative and with the descriptive type of the research. Result of theresearch identified the roles of ICAO as instrument, arena, and actor.